2018
DOI: 10.1101/287342
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Engineering targeted deletions in the mitochondrial genome

Abstract: ParagraphMitochondria are a network of critical intracellular organelles with diverse functions ranging from energy production to cell signaling. The mitochondrial genome (mtDNA) consists of 37 genes that support oxidative phosphorylation and are prone to dysfunction that can lead to currently untreatable diseases. Further characterization of mtDNA gene function and creation of more accurate models of human disease will require the ability to engineer precise genomic sequence modifications. To date, mtDNA has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…None of these mutations were embryonically lethal, allowing us to monitor the germline transmission of these edits in subsequent F1 generations during the future course of the study. It will be interesting to see if such high percentage of edits are able to withstand the oocyte selection of mutant mtDNA as observed previously with low heteroplasmy of mtDNA large-scale deletion in zebrafish 16 . Recently, a study describing mice editing with a custom designed DdCBE demonstrated base edits in mice F0 and F1 embryos albeit with maximum mtDNA editing efficiency up to 57% in F0 generation for one of the loci.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…None of these mutations were embryonically lethal, allowing us to monitor the germline transmission of these edits in subsequent F1 generations during the future course of the study. It will be interesting to see if such high percentage of edits are able to withstand the oocyte selection of mutant mtDNA as observed previously with low heteroplasmy of mtDNA large-scale deletion in zebrafish 16 . Recently, a study describing mice editing with a custom designed DdCBE demonstrated base edits in mice F0 and F1 embryos albeit with maximum mtDNA editing efficiency up to 57% in F0 generation for one of the loci.…”
Section: Discussionmentioning
confidence: 84%
“…To quantify the editing efficiency in vertebrate zebrafish embryos, a cassette containing DddA tox was cloned at the 3’ end of the C-terminus of the TALE domain in the linearized pk- idh2 GoldyTAL-lacZ-Fok1 destination vector. We identified a highly functional and sufficient mitochondrial targeting sequence from a reverse engineered in vivo protein trap in a nuclearly encoded mitochondrial protein 16,24 . This derived minimal mitochondrial targeting sequence (MTS) was highly active in zebrafish in vivo compared to previously described MTS sequences and was used to target an array of different proteins capable of interacting with the mtDNA genome 16 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, endonucleases imported into mitochondria can shift heteroplasmy ratios to alter mitochondria and cell functions by targeting specific sequences for destruction. However, these endonucleases are laborious to produce, are limited to certain mtDNA sequences, are inefficient, and do not yield homoplasmy ( Campbell et al, 2018 ; Yahata et al, 2017 ; Yang et al, 2018 ). Of note, a recent and exciting development using a bacterial cytidine deaminase, DddA, to edit mtDNA single-base sequences is tempered by low efficiency and an undesirable off-target rate ( Mok et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%